Immediate management of a stable patient with unstable pelvis - Juan Ramón Cano; José Manuel Bogallo; Alicia Ramirez; Enrique Guerado (EFORT Open Reviews, 2024)
The diagnosis of a traumatic unstable pelvis in a stable patient is a temporary concept depending on when we see the patient, as all patients presenting with hemorrhagic shock have hemodynamic stability until they become unstable. As a rule, the more unstable the pelvic fracture is, the higher the risk of bleeding and hemodynamic instability it has. Therefore, in unstable pelvic fractures, hemodynamic stability should be a diagnosis by exclusion. For bleeding detection in stable patients, an immediate one-stage contrast-enhanced CT scan is the appropriate diagnosis test; however, since CT scan radiation is always an issue, X-rays should be considered in those cases of hemodynamically stable patients in whom there is a reasonable suspicion that no unsafe bleeding is going on. Pelvic fracture classification is essential as usually there is an association between the injury mechanism, the fracture displacement, and the hemodynamic stability. Anteroposterior and, particularly, vertical traumatisms have much more proclivity to provoke major pelvic displacement and bleeding. The use of a pelvic binder, as early as possible including pre-hospital management, should be standard in high-impact blunt trauma patients independently of the trauma mechanisms. External fixation is the preferred method of stabilization in case of open fractures, and, in closed ones, when the schedule for definite osteosynthesis prolongs because of the patient’s general condition. If possible, immediate percutaneous sacroiliac screw insertion for unstable pelvic fractures produce excellent results even in open fractures.